Prevalence, Etiology, Diagnosis, Treatment and Complications of Supernumerary Teeth in The Pediatric Clinic - Watted, Nezar; Watted, Ali; Proff, Peter; Borbély, Peter; Ghoul, Rand; Abu Shilbayih, Hanali; Kolomvos, Nikolaos; Abu-Hussein, Muhamad (Journal of Neonatal Surgery, 2025)
Introduction: Hyperdontia is the condition of having supernumerary teeth, or teeth which appear inaddition to the regular number of teeth. The prevalence rates of supernumerary teeth in the permanent dentition amounts 0.1 -6.9%, and in deciduous dentition 0.4-0.8%. The presence of supernumerary teeth can be found in everyday dental practice. This study aimed to review current literature and present the aetiology, prevalence, diagnosis, treatment options and complications of supernumerary teeth. State of knowledge; Supernumerary teeth can be divided according to different criteria: by structure, tooth shape, location and number of additional teeth. The most common supernumerary tooth is mesiodens, which is an additional tooth located between the central incisors of the jaw. The aetiology of formation of supernumerary teeth is not yet fully known. At present, the most probable hypothesis for the development of hyperdontia is the hyperactivity of dental lamina. Supernumerary teeth may cause aesthetic and functional problems like delayed eruption, alterations in the eruptive pattern, shift in the midline, dental crowding, pathology in adjacent teeth, problems with correct occlusion. These problems are the most common reason for patients to report to their dentist. When an supernumerary tooth does not cause any troubles or aesthetic disorders, its detection is usually accidental during the X-rays examination. Treatment depends on the specific clinical situation. Making a diagnosis and developing an appropriate treatment plan often requires cooperation of many specialists. Conclusion; Supernumerary teeth may cause aesthetic deformities and functional impediments, therefore early diagnosis and interdisciplinary intervention are important to minimize consequences to the developing dentition. The clinicians should be mindful of such signs as delayed eruption, alterations in the eruptive pattern, shift in the midline, or dental crowding..